PROPOSED STRATEGY IN MANAGING DIRECT DIGITAL MARKETING CHANNEL FOR PT GARUDA INDONESIA (PERSERO) TBK (The Indonesian Journal of Business Administration, 2021)
The development of the digitalization today has encouraged various industries to develop electronic distribution channels in delivering products from manufactures to consumers. This is also happened at airline industry where electronic commerce (e-commerce) are very rapidly growing, almost 90% of Internet users in Indonesia make transactions on e-commerce. Evidenced by the emergence of Online Travel Agent (OTA), airline websites, mobile applications and other digital distribution channels drive this electrical commercial activity to be the right choice for consumers. Data shows that most aircraft passengers choose to make transactions through electronic sales channels. Based on the evaluation of Garuda Indonesia's flight ticket sales performance, the highest growth occurred in OTA of 56%. While sales transactions on mobile sites and applications decreased by 23%.This study aims to explore the problem of declining sales on direct/owned channel including airline websites and mobile applications, amidst the growth of e-commerce, especially OTA. By conducting external analysis including PESTEL and competitor analysis and combining the results of internal analysis that includes resources-based analysis and competitive advantage through the evaluation of Garuda Indonesia flight ticket marketing channels, the conclusion of business problems that occur.Alternative strategy in sales channel management is combined with marketing mix theory 4P's (Poduct, Pricing, Place, Promotion) to produce a comprehensive strategy proposal in managing airline-owned sales channels namely websites, mobile applications, and contact centers. The four main strategies are the integrated direct digital channel members, improving promotion on travel product and service, simplification of service menu displays on sites with a focus on signature products, and improving information technology performance. Keywords: Airline business, OTA, e-commerce, marketing mix